Is the students´ competence stimulated through Natural Science textbooks? Teacher perspectives and analysis of textbooks in the 1st and 2nd years of ESO - Raquel Romero Fernández; Mª Ángeles De las Heras Pérez; Gabriel Travé González (Arizona State University, 2020)
Since their implementation in the Spanish educational system, competencies occupy a relevant place, since they are the axis around which the other elements of the curriculum revolve. However, the competence development of secondary students does not seem to be the most desirable. Consequently, it is essential to study the elements involved in this problem as a first step to reverse this situation. Among these variables, we consider the textbook as an especially relevant element, due to its important presence in the classrooms and in principle, its obligatory, competency character. Therefore, the objective has been to analyze if the competence development of the students of the first cycle of secondary is favored by textbooks of Nature Sciences. For this purpose, a qualitative-quantitative methodological approach has been chosen, since on the one hand, the activities of the textbooks of three publishing houses with a large presence in the classrooms are examined and, on the other hand, the opinions of a group of professors as the main responsible for its use. The results show that the didactic sequence is inadequate, an appropriate diversity of resources is lacking, and the cognitive development promoted by the activities is low. Likewise, teachers state that competencies are not favored, due among other factors, to the rote learning promoted by said manuals, despite which it continues to be a resource of great relevance in their classes. Consequently, it would be necessary to review these from a competency-based approach and their use in the classroom, as well as a reflection on the requirements necessary for a change in educational policy, such as the introduction of competences, to reverse the classroom properly.